Decreased Insulin Sensitivity in Telomerase-Immortalized Mesenchymal Stem Cells Affects Efficacy and Outcome of Adipogenic Differentiation in vitro - Kulebyakin, Konstantin; Tyurin-Kuzmin, Pyotr; Efimenko, Anastasia; Voloshin, Nikita; Kartoshkin, Anton; Karagyaur, Maxim; Grigorieva, Olga; Novoseletskaya, Ekaterina; Sysoeva, Veronika; Makarevich, Pavel; Tkachuk, Vsevolod (Frontiers in Cell and Developmental Biology, 2021)
Modern biomedical science still experiences a significant need for easy and reliable sources of human cells. They are used to investigate pathological processes underlying disease, conduct pharmacological studies, and eventually applied as a therapeutic product in regenerative medicine. For decades, the pool of adult mesenchymal stem/stromal cells (MSCs) remains a promising source of stem and progenitor cells. Their isolation is more feasible than most other stem cells from human donors, yet they have a fair share of drawbacks. They include significant variability between donors, loss of potency, and transformation during long-term culture, which may impact the efficacy and reproducibility of research. One possible solution is a derivation of immortalized MSCs lines which receive a broader use in many medical and biological studies. In the present work, we demonstrated that in the most widely spread commercially available hTERT-immortalized MSCs cell line ASC52telo, sensitivity to hormonal stimuli was reduced, affecting their differentiation efficacy. Furthermore, we found that immortalized MSCs have impaired insulin-dependent and cAMP-dependent signaling, which impairs their adipogenic, but not osteogenic or chondrogenic, potential under experimental conditions. Our findings indicate that hTERT-immortalized MSCs may present a suboptimal choice for studies involving modeling or investigation of hormonal sensitivity.